ANALISIS PDRB, TINGKAT PENDIDIKAN DAN TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA SELATAN PERIODE 2004-2013 - SARI, SINDI PARAMITA; ANWAR, DEKY DEKY; DARUSSAMIN, DARUSSAMIN DARUSSAMIN (I-Economics, 2016)
One goal of development is to reduce poverty. Poverty is one the diseases in the economy, so it must be cured or reduced. The aim of this research is to analyze the influence of growth of PDRB, level of education, and level of unemployment to poverty level in province of South Sumatera periode 2004-2013. This research using quantitive descriptive method with multiple regression approach. This method is to determine and analyze how to influence of growth of PDRB, education, and unemployment to level of poverty level in province South Sumatera periode 2004-2013. The result showed that growth of PDRBvariable, education, and unemployment simultaneously influence to level of poverty in province South Sumatera. Partially PDRB and education have negative effect to poverty and unemployment has positive effect to poverty.Key Word: PDRB, Education, Unemployment, Level of Poverty.